Monthly expenditure of PTPTN loan receiver among Shah Alam university students / Nur Afza Faraheen Afizul, Aina Adriana Anizat and Che Norhalila Che Mohamed - Afizul, Nur Afza Faraheen; Anizat, Aina Adriana; Che Mohamed, Che Norhalila (Universiti Teknologi MARA, Negeri Sembilan, 2024)
National Higher Education Fund Corporation, also known as Perbadanan Tabung Pendidikan Tinggi Nasional (PTPTN) is one of the study loans taken by students from public and private institutions to finance their cost of living throughout their studies. The specific loan amount has not been revised despite the significant increase in the cost of living, affecting individuals across demographics and causing substantial financial strain. Researchers aim to investigate how students at public and private institutions allocate their overall PTPTN loan. Descriptive statistics were used to describe the total monthly expenditure in nine categories. Public university students exhibited higher variability and maximum expenditure in categories such as food and beverages, savings, transportation, communication, and health. An independent sample t-test showed no significant difference in the average monthly expenditure between public and private university students.